ANALYZING EFL LEARNERS' NEEDS FOR VOCABULARY LEARNING MATERIALS - Yudi Basuki; Astried Damaynti; Sri Utami Dewi (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2018)
Vocabulary is important; it is as the core of language complexities and as a starting point of those who are learning a new language. The purpose of this study was to identify the EFL learners’ needs for learning English vocabulary. The identification of learners’ needs was conducted to all active students of English Language education studying program of STKIP PGRI Trenggalek. It used the open-closed questionnaire. Research findings of analyzed data found a number of the students’ crucial target and learning needs for vocabulary learning which was ordered with its complexity, depth, prerequisite and relevancy such as; part of speech, morphemes, affixation, word families, collocations, synonym and antonym, homophone and homograph, word in comparison, punctuations, forming new words (blending, compounding, clipping, acronym), phrases, idioms and a special material of strategies of vocabulary learning. In addition, all mentioned materials were needed to be presented in a contextual, meaningful and useful way.